Presentación - Salazar Mejía, Fernando (Ratio Juris (UNAULA), 2017)
Although Ratio Juris was born as a magazine profiled towards the dissemination of multiple reflections of socio-legal nature, connected at the same time with other fields of knowledge, in its latest publications we have been redimensioning the contents of the same, consistent with the mission of the magazine. In other words, it is focused on disseminating knowledge produced by research, in the national and international contexts, in subjects related to socio-legal topics.